Practical Tips in Urology - Rané, Abhay; Turna, Burak; Autorino, Riccardo; Rassweiler, Jens J. (Springer London : Imprint: Springer, 2017)
This book is a compact, illustrated reference which provides the reader with practical tips and advice in managing day-to-day urological issues encountered in a clinical setting. Practical Tips in Urology draws on practical experience and offers useful information that is often lacking in didactic textbooks of urology and in journal articles. The chapters provide tips in dealing with urological emergencies, elective surgery and common outpatient consultation problems, among other things. Written by experts in the field, Practical Tips in Urology is key reading for all practicing urologists and residents in training.- Resumé vydavatel